2008
DOI: 10.1088/0951-7715/22/1/002
|View full text |Cite
|
Sign up to set email alerts
|

On a novel integrable generalization of the nonlinear Schrödinger equation

Abstract: We consider an integrable generalization of the nonlinear Schrödinger (NLS) equation that was recently derived by one of the authors using bi-Hamiltonian methods. This equation is related to the NLS equation in the same way that the Camassa Holm equation is related to the KdV equation. In this paper we: (a) Use the bi-Hamiltonian structure to write down the first few conservation laws. (b) Derive a Lax pair. (c) Use the Lax pair to solve the initial value problem. (d) Analyze solitons.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
170
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(174 citation statements)
references
References 16 publications
1
170
0
3
Order By: Relevance
“…In optics, the FL equation models the propagation of nonlinear light pulses in monomode optical fibers when certain higher order nonlinear effects are taken into consideration [36]. The complete integrability of the FL equation has been exhibited by using the inverse scattering transform (IST) method [37]. Especially, a Lax pair and a few conservation laws related to it have been found clearly using the bi-Hamiltonian structure and the multisoliton solutions have been obtained by using the dressing method [38].…”
Section: Open Accessmentioning
confidence: 99%
“…In optics, the FL equation models the propagation of nonlinear light pulses in monomode optical fibers when certain higher order nonlinear effects are taken into consideration [36]. The complete integrability of the FL equation has been exhibited by using the inverse scattering transform (IST) method [37]. Especially, a Lax pair and a few conservation laws related to it have been found clearly using the bi-Hamiltonian structure and the multisoliton solutions have been obtained by using the dressing method [38].…”
Section: Open Accessmentioning
confidence: 99%
“…We show that these linear equations can be nonlinearized in a few simple steps to uniquely recover the full set of integrable equations. The first step is to note that linear equations (4), (5), and (6) fix the corresponding scaling dimension…”
Section: Nonlinearization Schemementioning
confidence: 99%
“…On the other hand, in addition to the well-known Camassa-Holms and Degasperis-Procesi equations, some other unusual new integrable equations were recently discovered, namely, the KdV6 [4], LF DNLS [5], mKdV-SG [10], and higher mKdV [11] equations. We realized that these uncommon equations are merely particular cases of general integrable perturbations of the AKNS-Zakharov-Shabat and the KN systems [6]- [8].…”
Section: Integrable Perturbation Through Nonholonomic Deformationmentioning
confidence: 99%
See 1 more Smart Citation
“…Related results can also be directly applied to (1.1) and (1.3) since the existence of these simple transformations among them. It is shown that (1.4)/(1.5) is a completely integrable nonlinear partial differential equation possessing Lax pair, bi-Hamiltonian structure, and soliton solutions [5,[16][17][18]. One of the most remarkable feature of the FL equation is that it possesses various kinds of exact solutions such as solitons, breathers, etc..…”
Section: Introductionmentioning
confidence: 99%